2009
DOI: 10.3176/oil.2009.3s.14
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Scenarios for the Baltic States and Marginal Energy Technology in Life Cycle Assessments - A Case Study of Energy Production From Municipal Waste Incineration

Abstract: In the present study two different sets of assumptions for future power production scenarios, one based on conventional technologies and another assuming a more sustainable energy oriented electricity production, for the Baltic States are analysed to identify the possible marginal electricity sources which could be used in consequential Life Cycle Assessment (LCA) studies in these countries. The environmental impacts of electricity production often account for a major portion of the total environmental burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The marginal energy supply (in particular electricity supply), is reported to strongly affect the results of LCA analysis (Kløverpris et al, 2008;Moora and Lahtvee, 2009) and hence, a study of the environmental burden of the scenarios analysed have been performed according to different energy technologies for indirect and avoided activities.…”
Section: Uk Future Energy Scenarios Of Electricity and Natural Gas MIXmentioning
confidence: 99%
“…The marginal energy supply (in particular electricity supply), is reported to strongly affect the results of LCA analysis (Kløverpris et al, 2008;Moora and Lahtvee, 2009) and hence, a study of the environmental burden of the scenarios analysed have been performed according to different energy technologies for indirect and avoided activities.…”
Section: Uk Future Energy Scenarios Of Electricity and Natural Gas MIXmentioning
confidence: 99%
“…Therefore, it would be good to study the possible change in the composition of waste and its possible impact on the results. Also the future energy source in Estonia is assumed to change including more renewable and nuclear energy while the share of oil shale is assumed to decline [23]. Thus, it would be interesting to analyse how a possible change of the marginal energy source would affect the net GHG emissions, especially the relative effects of waste incineration.…”
Section: Discussionmentioning
confidence: 99%
“…All of the reviewed case studies expanded the product system boundary by either increasing unit processes or including relevant products and co-products. Some studies made it very clear on the inclusion of extended unit processes [22][23][24][25][26], while others did not clearly identify the unit processes of a product system's life cycle [27][28][29][30][31][32][33][34]. In terms of products and co-products, the system boundary was extended to at least two products in all reviewed studies.…”
Section: System Boundarymentioning
confidence: 99%
“…Examples of the mutatis mutandis assumption can be found in several studies [23][24][25][26][27][28][29][30][31][32][33][34][40][41][42][43][44][45] (Refer to Table 2). In these studies, the marginal products or technologies were identified, with determined affected scales.…”
Section: System Boundarymentioning
confidence: 99%